Localization of Mental Foramen in Panoramic Radiographs of 18-30 Year Olds: A Hospital Based Study - Luitel, A.; Rimal, J.; Maharjan, I. K.; Shrestha, A.; Tamang, R. (Kathmandu University Medical Journal, 2020)
Background The position of the mental foramen demonstrates anatomical variations, although typically it is reported to be either between the apices of the first and second premolars or below the apex of the second premolar. Objective To determine the radiographic position of mental foramen in relation to Premolar crown and apex, in panoramic radiographs. Method Following ethical approval a retrospective study was conducted in 510 panoramic radiographs of 18-30 year olds from archives of Department of Oral Medicine and Radiology. The position of mental foramen was scored using crown and apex scores according to scoring criteria given by Jasser and Nwoku, 1998. Descriptive statistics was calculated and Chi-square test was applied to assess variation in position of mental foramen between genders and right and left side of mandible. Kappa statistics was applied to assess intra-observer reliability. Result The most common scoring for position of mental foramen on right side crown and apex was 3 (49.4%) followed by 4 (45.9%). Similarly, on left side the most common score for crown and apex was 3 (50.8%) followed by 4 (44.3%). There was no statistically significant difference in position between the genders. Comparing the right and left sides, the position was symmetrical in 83.3% for crown and apex scores. The Kappa values indicated good agreement for intraobserver reliability. Conclusion The most common position for the mental foramen is between the first and second premolar teeth; though, anatomical variations are seen.